Harrison's gastroenterology and hepatology 2026-02-16T07:30:02+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Fauci, Anthony S., 1940-; Harrison, Tinsley Randolph, 1900-1978; Langford, Carol A.; Longo, Dan L. (Dan Louis), 1949- (McGraw-Hill Medical, 2013)

(untitled)
Featuring a collection of chapters on gastroenterology and hepatology from Harrison's Principles of Internal Medicine, Eighteenth Edition and the companion DVD, this concise clinical companion also includes updates and new developments, and board review questions. It is ideal for the classroom, wards, or exam/certification preparation. Features: full-color presentation; content derived from Harrison's, the world's leading and most trusted medical text; convenient, carry-anywhere presentation